Land-use conflicts between biodiversity conservation and extractive industries in the Peruvian Andes - Bax, Vincent; Francesconi, Wendy; Delgado, Alexi (Elsevier, 2019)
The exceptional endemic species richness found in the Tropical Andes is being subjected to high rates of environmental degradation and natural resources exploitation. While many forms of land-cover change and other impacts on species are difficult to control through environmental regulations, governments usually determine how and where extractive industries can take place. This study examines potential conflict between the location of extractive industry activities and biodiversity conservation in the Peruvian Andes. Using geographic information systems, we carry out overlay analyses to determine the spatial congruence between mineral mining, hydrocarbon and logging concessions, on the one hand, and the distribution of protected areas and endemic vertebrate species on the other. The results show that regional protected areas extensively overlap with resource concessions. Furthermore, 16% of endemic species hotspots concur with current concessions, while the geographical distribution of 21 endemic vertebrate species overlap by more than 90% with concession areas. To reconcile conservation and economic development objectives in the future, the geographical distribution of biodiversity, and in particular of endemic species, needs to be considered in natural resources planning and land-use/management activities.